2017
DOI: 10.1145/3134692
|View full text |Cite
|
Sign up to set email alerts
|

Service Providers of the Sharing Economy

Abstract: Many "sharing economy" platforms, such as Uber and Airbnb, have become increasingly popular, providing consumers with more choices and suppliers a chance to make profit. They, however, have also brought about emerging issues regarding regulation, tax obligation, and impact on urban environment, and have generated heated debates from various interest groups. Empirical studies regarding these issues are limited, partly due to the unavailability of relevant data. Here we aim to understand service providers of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
(64 reference statements)
0
22
0
1
Order By: Relevance
“…Recent work has found that young and well‐educated individuals are overrepresented among active users. On average, users have rather low income and tend to be rather male than female (European Commission, ; Ke, ; PwC, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has found that young and well‐educated individuals are overrepresented among active users. On average, users have rather low income and tend to be rather male than female (European Commission, ; Ke, ; PwC, ).…”
Section: Discussionmentioning
confidence: 99%
“…On average, users have rather low income and tend to be rather male than female (European Commission, 2017; Ke, 2017;PwC, 2015).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies in HCI on monetized network hospitality have examined the hospitality exchange processes that take place via Airbnb [22,24,25,28,30,34,41]. Ma et al studied the type of content that Airbnb hosts self-disclose in their profiles and showed that hosts optimize their disclosures for trustworthiness by revealing more assessment signals than conventional ones [30].…”
Section: Study Context: the Work Of Hostingmentioning
confidence: 99%
“…Studies exist that look into hosts' motivation to participate in online hospitality networks [73,121]. Such research approaches deal with drivers for renting out [70,73,121] and analyze the importance of monetary transactions in hospitality exchange networks [66]. Other studies were concerned with hosts' trustworthiness [48,83].…”
mentioning
confidence: 99%